Nanotechnology in leukemia: diagnosis, efficient-targeted drug delivery, and clinical trials - Maha M. Salama; Nora M. Aborehab; Nihal M. El Mahdy; Ahmed Zayed; Shahira M. Ezzat (European Journal of Medical Research, 2023)
Abstract Leukemia is a group of malignant disorders which affect the blood and blood-forming tissues in the bone marrow, lymphatic system, and spleen. Many types of leukemia exist; thus, their diagnosis and treatment are somewhat complicated. The use of conventional strategies for treatment such as chemotherapy and radiotherapy may develop many side effects and toxicity. Hence, modern research is concerned with the development of specific nano-formulations for targeted delivery of anti-leukemic drugs avoiding toxic effects on normal cells. Nanostructures can be applied not only in treatment but also in diagnosis. In this article, types of leukemia, its causes, diagnosis as well as conventional treatment of leukemia shall be reviewed. Then, the use of nanoparticles in diagnosis of leukemia and synthesis of nanocarriers for efficient delivery of anti-leukemia drugs being investigated in in vivo and clinical studies. Therefore, it may contribute to the discovery of novel and emerging nanoparticles for targeted treatment of leukemia with less side effects and toxicities.